Стелла искушает судьбу: [роман] / Ирина Львова - Львова Ирина (Черная метка, 2000)
Экземпляры: Ф. 2 (20200113) / Инвентарный номер: 47488 / Цена: 15.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Л 89 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44